Influence of Sm3+ doping on the dielectric properties of CaCu3Ti4O12 ceramics synthesized via autocombustion - Lopera, Alex; Ramirez, Miguel Angel [UNESP]; Garcia, Claudia; Paucar, Carlos; Marin, Jairo (Elsevier B.V., 2014)
Ca-1 -xSmxCu3Ti4O12 (x = 0.0, 0.2, 03) electronic ceramics were fabricated via the chemical route using metal nitrate solutions in order to improve the dielectric properties of this ceramic. X-ray diffraction (XRD) analysis indicated the formation of a single CaCu3Ti4O12 (CCTO). Grain size of the samples doped with Sm3+ was in the range of 1-2 mu m, as opposed to 50-100 mu m in the pure samples of CCTO. The cutoff frequency with the doping was remarkably shifted, from 1 MHz (pure CCTO) to 10 MHz (doped CCTO). Meanwhile, the real dielectric (epsilon(r)) and imaginary dielectric (epsilon '') constants showed a decrease as the doping was increased. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: CCTO; Samarium; Citrate-nitrate route; Dielectric properties